2021
DOI: 10.1007/s12350-019-01659-2
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET in possible cardiac sarcoidosis: Right ventricular uptake and high total cardiac metabolic activity predict cardiovascular events

Abstract: Background. Cardiac involvement accounts for the majority of morbidity and mortality in sarcoidosis. Pathological myocardial fluorodeoxyglucose (FDG)-uptake in positron emission tomography (PET) has been associated with cardiovascular events and quantitative metabolic parameters have been shown to add prognostic value. Our aim was to study whether the pattern of pathological cardiac FDG-uptake and quantitative parameters are able to predict cardiovascular events in patients with suspected cardiac sarcoidosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
1
25
0
2
Order By: Relevance
“…Indeed, the association between a high tCMA and RV pathological FDG-uptake should be considered as a significant risk marker in patients with suspected CS. 11 In accordance with these results, Ahmandian et al 14 showed that a high tCMA was an independent predictor of cardiovascular events in CS patients. Similarly, in a recent study by Omote et al, CS patients with RV FDG-uptake showed notably higher cardiac metabolic volume (CMV), total lesion glycolysis (TLG), LV standardized-uptake-value (SUV) max, LV involvement, and cardiac adverse events than those without.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Indeed, the association between a high tCMA and RV pathological FDG-uptake should be considered as a significant risk marker in patients with suspected CS. 11 In accordance with these results, Ahmandian et al 14 showed that a high tCMA was an independent predictor of cardiovascular events in CS patients. Similarly, in a recent study by Omote et al, CS patients with RV FDG-uptake showed notably higher cardiac metabolic volume (CMV), total lesion glycolysis (TLG), LV standardized-uptake-value (SUV) max, LV involvement, and cardiac adverse events than those without.…”
mentioning
confidence: 60%
“…9 Obtaining a complete FDG-uptake suppression in normal myocardium through dietary protocols permits a more confident diagnosis of cardiac involvement; so it is important to check the rate of cardiac suppression obtained in own Center and modify/ lengthen the dietary protocol, accordingly. Indeed, although several patterns of normal left-ventricular (LV) FDG-uptake have been described, 10,11 non-homogeneous cardiac distribution of radiotracer may rise interpretative doubts; thus, a complete and robust clinical assessment is mandatory to determine the most probable diagnosis. In the current issue of the Journal, Tuominen et al performed a retrospective analysis of 137 patients who underwent 18 F-FDG-PET/CT imaging for suspected CS evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the PET study by Tuominen et al, a subset of patients underwent CMR imaging; no adverse events were reported in patents who had no LGE, confirming an excellent negative predictive value of this finding (43).…”
Section: Cmrmentioning
confidence: 79%
“…Patients with pathologic right ventricular uptake had significantly higher total cardiac metabolic activity than those without right ventricular uptake. Therefore, the combination of pathologic right ventricular uptake and high total cardiac metabolic activity should be considered a significant risk factor in patients with CS (43,44).…”
Section: Therapeutic and Prognostic Considerations Of Cardiac Pet Andmentioning
confidence: 99%